2021
DOI: 10.3390/info12100397
|View full text |Cite
|
Sign up to set email alerts
|

Pear Defect Detection Method Based on ResNet and DCGAN

Abstract: To address the current situation, in which pear defect detection is still based on a workforce with low efficiency, we propose the use of the CNN model to detect pear defects. Since it is challenging to obtain defect images in the implementation process, a deep convolutional adversarial generation network was used to augment the defect images. As the experimental results indicated, the detection accuracy of the proposed method on the 3000 validation set was as high as 97.35%. Variant mainstream CNNs were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Nowadays, thanks to some researchers incorporating new modules and improvements in related studies, such as agriculture, industry, and medicine, multiple new CNN methods are being developed. In the agricultural field, for example, an optimized CNN model was utilized to detect pear defects; more specifically, a deep convolutional adversarial generation network was adopted to expand the diseased images [30]. Experimental results showed that the detection accuracy of the presented method on the validation set reached 97.35%.…”
Section: Related Workmentioning
confidence: 99%
“…Nowadays, thanks to some researchers incorporating new modules and improvements in related studies, such as agriculture, industry, and medicine, multiple new CNN methods are being developed. In the agricultural field, for example, an optimized CNN model was utilized to detect pear defects; more specifically, a deep convolutional adversarial generation network was adopted to expand the diseased images [30]. Experimental results showed that the detection accuracy of the presented method on the validation set reached 97.35%.…”
Section: Related Workmentioning
confidence: 99%
“…The inference speed exceeded 29 frames per second. In the case of pear flaws detection, scholars developed an upgraded CNN model; more specifically, a deep convolutional adversarial generation network was used to extend the diseased pictures [34]. According to the experimental data, the detection accuracy of the proposed technique was 97.35% (in the validation).…”
Section: Related Workmentioning
confidence: 99%
“…In the deep residual network (ResNet) proposed by He et al [26] in 2015, the addition of identity mapping solves the problem that deep network models are difficult to train. In the last few years, ResNet has been widely used in various classification tasks [27][28][29][30] with strong capabilities. On this basis, a Multi-SE-ResNet34 model combined with the attention mechanism is proposed, and the structure is shown in Figure 4.…”
Section: Multi-se-resnet34 Modelmentioning
confidence: 99%